Ordinary language film studies - Klevan, A (Dutch Association of Aesthetics, 2020)
This essay explains Ordinary Language Philosophy (OLP), because it is relatively unfamiliar to those working in the field of Film-Philosophy, and proposes it as beneficial to film study. OLP provides us with a method of philosophising in relation to films that (1) is not theoretical, paradigmatic or thematic, and is therefore potentially unrestrained because it is not a priori or determining; that (2) is context sensitive, proceeding on a case-by-case basis, while also capable of synoptic overview (through connective analysis); that (3) encourages conceptual clarification and responsive articulation in order to present a perspicacious picture of individual films and our experience of them; and that (4) can act therapeutically by uncoupling us from unhelpful linguistic attachments that may restrict, helping us to see anew.